PENGGUNAAN FUNGSI "SOLVER" DALAM FORMULASI PAKAN TERMURAH UNTUK PETERNAK SAPI PERAH SKALA KECIL - IGM, Budiarsana (Informatika Pertanian, 2016)
Smallholder dairy farmers in Indonesia are very limited by the availability of quantity and quality of the feedstuff, especially in dry season. Sources of protein from legumes and non-conventional materials can be found around the area and used as feed ingredients for dairy cows. However, the major problem is in feed formulation for nutritionally balanced ration and with the cheapest cost. This paper outlines a step-by-step procedure in feed formulation based on Excel program for dairy farmers. The steps were performed to provide assurance that the resulting balanced ration was according to the targeted performance and at least cost. Also, users could control the process of formulating the ration. Examples were given by utilizing legumes and the results indicated that the reduction in feed cost was very real, as much as 10-20% when compared to the concentrated feed commonly used by farmers at a price of Rp1420/kg. The formulation method prepared by the program SOLVER can be recommended for use by dairy cattle ranchers individually or with assistance from Extension workers. Farmers are expected to be able to formulate their feed easily in order to get the least cost formula using feedstuff available in abundance, to minimize production cost, and to optimize feed management at small scale farming level.